Legal and Ethical Regulation on Childcare Digital Health System in Nigeria and Uganda: Issues and Challenges - Aidonojie, Paul Atagamen; Nurhasanah, Siti; Kasmawati, Kasmawati; Aidonojie, Esther Chetachukwu; Ekpemisi, Collins; Atim, Amos Godfrey (Faculty of Law Universitas Trunojoyo Madura, 2026)
The implementation of digital technologies in the healthcare system for children has a lesser but still noticeable effect on the health systems of Nigeria and Uganda. Digital tools such as electronic pediatric health records, tele-pediatric, m-health apps, and data-driven diagnostic platforms have been implemented. However, children's vulnerability in the digital healthcare domain has been significantly increased by the new technologies. The research scrutinizes the current insufficient and disorganised legal and ethical systems that control child digital healthcare in Nigeria and Uganda. The research employs a doctrine-based method, utilising the PRISMA Guide to systematically identify, screen, and analyse relevant laws, policies, and academic literature on children's rights. The results indicate that both countries have generic health and data protection laws that can be applied to digital health in general, but regulations and ethical standards (such as consent, data privacy, cybersecurity, parental authority, and professional liability) specific to children remain underdeveloped and poorly enforced, specifically in Nigeria. The study makes the case for child-friendly digital health legislation, clear consent standards, rigorous institutional oversight, and regional collaboration to ensure children's rights and welfare in digital healthcare systems.